2000
DOI: 10.1034/j.1399-3046.2000.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired exercise parameters in pediatric heart transplant recipients: Comparison of biatrial and bicaval techniques

Abstract: The exercise performance of pediatric heart transplant recipients and the effects of bicaval anastomosis were studied in 19 children using a Bruce protocol. Although all children had decreased exercise capacity and heart rates when compared with normals, the bicaval anastomosis patients had similar endurance and peak heart rates as the standard biatrial group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…5 In the pediatric literature, there are recent reports of at least partial reinnervation over time, 13,34 but other pediatric studies have not supported these findings. [22][23][24][25][26] Similar to these latter studies, our population did not demonstrate any change in PHR over time; therefore, chronotropic impairment cannot account for the decline in aerobic capacity over time. Further, we cannot explain the relatively low PHR or lack of improvement over time as a medication effect because only 1 patient was taking a ␤-blocker.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…5 In the pediatric literature, there are recent reports of at least partial reinnervation over time, 13,34 but other pediatric studies have not supported these findings. [22][23][24][25][26] Similar to these latter studies, our population did not demonstrate any change in PHR over time; therefore, chronotropic impairment cannot account for the decline in aerobic capacity over time. Further, we cannot explain the relatively low PHR or lack of improvement over time as a medication effect because only 1 patient was taking a ␤-blocker.…”
Section: Discussionsupporting
confidence: 66%
“…Cross-sectional studies have shown that, similar to adult HTX patients, pediatric HTX survivors have diminished aerobic capacities compared with otherwise healthy children. [22][23][24][25][26] To our knowledge, no studies to date have longitudinally evaluated aerobic capacity after HTX in the pediatric population. We now report the first retrospective analysis of exercise performance findings from a longitudinal study of 28 pediatric HTX patients and the association of aerobic capacity with echocardiographic measures of graft function.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Our results show that exercise capacity in subjects after cardiac transplantation during infancy is within the range of low normal, defined as being within 1 standard deviation of the control group. Additionally, the maximum HR and peak VO 2 from this study are greater than that of data available from studies performed in older children and in adolescent recipients (Table 3).…”
Section: Discussion Exercise Capacitymentioning
confidence: 82%
“…Participants in a multicenter study of adolescent HTx recipients reported excellent physical QOL, but compared with a normative sample of adolescents, 3 they had significantly lower QOL scores for emotional, social, and school functioning that was associated with several factors, including medication side effects and level of family conflict, demonstrating that multiple variables influence adolescent health-related QOL over time. 3,11,12 We also expected decreased exercise and work capacity in our study cohort 13,14 as well as diminished psychologic well-being related to late complications such as kidney transplant and other comorbidities. 2,15,16 This was the case in a previous study by Littlefield et al, 17 wherein few adult solid-organ transplant recipients reported that they were working or in school after transplant.…”
Section: Quality Of Lifementioning
confidence: 89%